Countries and concepts politics, geography, culture - Roskin, Michael G. (Pearson, 2013)
An introduction to the concepts and vocabulary of comparative politics using a country-by-country analysis and case studies. This edition has been updated to include elections, prime ministers and relevant political issues of the late-20th century.